Redefining religion? A critical Christian reflection on CRL Rights Commission's proposal to regulate religion in South Africa - Banda, Collium (Verbum et ecclesia, 2019)
What do the recommendations of the Commission for the Promotion and Protection of the Rights of Cultural, Religious and Linguistic Communities (CRL Rights Commission) to regulate religion in South Africa reflect about the commission's understanding of religion in the country? From a Christian theological perspective, the article critically engages the understanding of religion that emerges from the findings and recommendations of the CRL Rights Commission on the state of religion in South Africa as contained in its 2017 report. The article first examines the different responses to the CRL Rights Commission's recommendations by writers concerned with freedom of religion and human rights in South Africa. Further, the commission's investigations, findings and recommendations are critically examined. This is followed by deciphering attitudes towards religion that emerge from the commission's recommendation for the regulation of religion in South Africa. The article closes by highlighting some possible dangers of regulating religion in a context riddled by economic inequality such as in South Africa.Intradisciplinary and/or interdisciplinary implications: This article brings into dialogue Christian theology, religious freedom, human rights and the constitution, philosophy and sociology of religion to reflect on the essence of religion and freedom of religion in the context of undesirable and dangerous religious practices.